Epidemiology of 911 Calls for Opioid Overdose in Nogales, Arizona - Melody Glenn; Darien Stratton; Keith Primeau; Amber Rice (Western Journal of Emergency Medicine)
Objective: Drug overdose is the leading cause of unintentional death in the United States, and individuals identifying as BIPOC (Black, indigenous and people of color) and those of low socioeconomic status are over-represented in this statistic. The US-Mexico border faces several unique challenges when it comes to healthcare and the drug overdose crisis, due in large part to health inequities. Although the US Centers for Disease Control and Prevention recommends that overdose prevention programs address health inequities, little is known about opioid overdoses in this rural, primarily Spanish-speaking region. As emergency medical services (EMS) records collect countywide data, they represent a high-quality source for epidemiologic surveillance. Methods: We conducted a retrospective chart review based on a local quality assurance program in which two years of EMS records were reviewed with the primary objective of characterizing patients receiving prehospital care for opioid overdoses in a rural, borderland community, and the secondary objective of characterizing EMS’s fidelity to a naloxone distribution protocol. We included electronic patient care records for analysis if they included the EMS clinician’s impression of overdose, opiate abuse, or opiate-related disorder from November 1, 2020–October 31,2022. The following data points were abstracted: date; patient initials/gender/age; police presence; response location; bystanders on scene; naloxone administration prior to EMS arrival; distribution of naloxone kit (yes/no); substance reported; and disposition. We analyzed descriptive statistics. Results: A total of 74 cases met inclusion criteria over two years with the majority of cases involving men (82%) with a median age of 28. Almost half of overdoses occurred at private residences (46%), and slightly more than half (57%) reported fentanyl use prior to overdose. Family or friends were usually (64%) on scene, and law enforcement was often (77%) the first 911 to arrive. Naloxone was administered on scene in almost all cases (91%), usually by EMS (44%) or law enforcement (43%). The EMS clinicians distributed naloxone kits at 61% of calls. Conclusion: Opioid overdoses along the US-Mexico border occurred primarily among young men using illicit fentanyl in private residences. Although family/friends were often present, they rarely administered naloxone. Law enforcement was often the first 911 responder to arrive. Emergency medical services is a suitable setting for naloxone distribution programs.